二项式定理怎么做啊啊

2025-02-22 10:02:52
推荐回答(1个)
回答1:

1
[(x-1)^2-4]^4=(x-1)^8-16(x-1)^6+6*16(x-1)^4-4*64(x-1)^2+256
=(x^8-8x^7+28x^6-56x^5+70x^4+56x^3+28x^2+8x+1)
-16x^6+96x^5-240x^4+320x^3-240x^2+96x-16
+96x^4-384x^3+576x^2-384x+96
-256x^2+512x-256+256
=x^8-8x^7+12x^6+40x^5-74x^4-8x^3+88x^2+598x+81

2
(1+√2)^5=1+5√2+10*2+10*2√2+5*2+4√2=31+29√2
a+b=60

3
-1-2-3-4-5=-15

4
(1-0.01)^10=[(1-0.01)^5]^2
(1-0.01)^5=1+5*0.01-10*(0.01)^2+10*(0.01)^3-5*(0.01)^4+0.01^5
≈1.0499
(1.0499)^2=(1+0.0499)^2=1+2*0.0499+0.0499^2
≈1.0998
1.10